1998
DOI: 10.1002/(sici)1098-2752(1998)18:7<410::aid-micr4>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Replantation in children

Abstract: The rates of survival of the amputated part and the functional outcomes were studied retrospectively after 13 replantations and 12 revascularizations in 25 children. The ages of the patients ranged from 2 to 15 years (mean, 6.4 years). The average duration of follow-up was 4.2 years (range, 2 to 7 years). The survival rate was higher after revascularization (94.6%) than after replantation (84.6%). Sensory recovery of all digits was satisfactory. The mean growth rate of replanted digits relative to contralatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Nevertheless, several pediatric series have reported high survival rates ranging from 64.5% to 100% as reported in Table 3, with different mechanisms or no precision about the proportion of avulsions. 2,4,5,14,25 Saies et al 26 reported the main study about amputations in children including 120 cases with 73 amputations and 89 revascularizations in patients under 16 years of age. Differentiating the various mechanisms of injury, they reported a lower rate of survival after an avulsion or crush (53% after replantation compared with 63% in the overall series and 75% after revascularization compared with 88% overall).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, several pediatric series have reported high survival rates ranging from 64.5% to 100% as reported in Table 3, with different mechanisms or no precision about the proportion of avulsions. 2,4,5,14,25 Saies et al 26 reported the main study about amputations in children including 120 cases with 73 amputations and 89 revascularizations in patients under 16 years of age. Differentiating the various mechanisms of injury, they reported a lower rate of survival after an avulsion or crush (53% after replantation compared with 63% in the overall series and 75% after revascularization compared with 88% overall).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of venous reconstruction, there were 5 cases of major venous congestion to which we attributed the failure of revascularization despite the use of venous drainage techniques and leeches. 14,23 The level of injury, with regard to both bone amputation and the site at which the skin is cut, has been extensively addressed in the literature. 19,[37][38][39] Some investigators have concluded that there is no association between the level of injury and the rate of survival, 6,26,40 whereas they found that the restoration of total active motion was significantly better when the amputation was distal to the insertion of the flexor digitorum superficialis tendon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviewing the relevant literature revealed that five papers about big toe replantations have been published according to the Medline index. [2][3][4][5][6][7][8] Nine of ten completely amputated big toes were replanted successfully. The longest follow-up period after replantation was 6.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, it is also known clinically that there is an impairment of various degrees in longitudinal bone growth in children following limb or finger replantation, when compared to the intact side. [2][3][4][5] Apart from the role played by injury situation and level of amputation, this impairment is considered to be due mainly to the effect of ischemia, and some reports have been published on experimental studies being carried out on the effects of ischemia. [6][7][8][9][10] The critical length of time of ischemia in which growth disturbance may occur has varied from 2 to 8 hr in some experimental studies, but the clear conclusions on the cause of this impairment have not been determined.…”
mentioning
confidence: 99%